Examining the Effects of Environmental Concern, Attitude, and Perceived Behavioral Control on Generation Z’s Purchase Intention for Recycled Fashion Products - Aziza Safira Farhan; Ratni Prima Lita; Maruf Maruf (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
The fashion industry significantly contributes to environmental degradation, particularly through textile waste and carbon emissions. Recycled fashion products have emerged as an alternative to promote sustainable consumption. Although Generation Z is recognized for having a high level of environmental concern, the dynamics underlying the formation of purchase intention toward recycled fashion products require deeper understanding. This study aims to examine the effects of environmental concern, attitude, and perceived behavioral control on Generation Z’s purchase intention toward recycled fashion products. This research adopts a quantitative approach using a survey method involving 115 Generation Z respondents who are familiar with recycled fashion products. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) 4.0. The findings indicate that environmental concern, attitude, and perceived behavioral control have positive and significant effects on purchase intention. These results reinforce the applicability of the Theory of Planned Behavior in explaining purchase intention within the sustainable fashion context and highlight the importance of psychological factors and perceived behavioral control in shaping Generation Z’s purchasing decisions.